A Comprehensive Analysis of Ischemic Brain Injury in Rodent Models That is Pertinent to Clinical Stroke in Actual Humans (Journal of Pharmaceutical Negative Results, 2022)
The second largest cause of death worldwide and a key contributor to disability among survivors is stroke. All 152 human clinical trials undertaken over the past 22 years found that almost none of the 56 neuroprotective medicines that had shown promise in preclinical testing were massive failures.[1-3] The links between results and underlying vascular variability, physiologic regulation, and usage of the comorbidity model are particularly stressed. In this review, we made an effort to establish a connection between the many clinical stroke disorders that exist in humans and the best rodent stroke models. In addition, the review emphasizes the importance of using a variety of preclinical models to comprehend the pathophysiological mechanisms that underlie stroke and to identify novel, safe, and efficient neuroprotective drugs to address this potentially fatal healthcare issue. We seek to advance translational research for the creation of novel treatments for the acute and subacute periods after stroke by identifying the benefits and drawbacks of animal models of stroke and the flaws of prior clinical studies.